Leaf architecture and anatomy of Asteraceae species in a xerophytic scrub in Mexico City, Mexico - Rivera, Patricia; Terrazas, Teresa; Rojas-Leal, Alicia; Villaseñor, José Luis (Instituto de Ecología, A.C., 2019)
Background and Aims: Leaf architecture and anatomy in the Asteraceae family are extremely diverse and have been studied from ecological, physiological and evolutionary perspectives. The aims of this study are to describe in detail leaf architecture and anatomy for 61 species belonging to 13 tribes of Asteraceae inhabiting a xerophytic scrub in Mexico City, Mexico and to discuss characters common to these tribes.Methods: Mature and undamaged leaves of 61 species of Asteraceae were collected in southwestern Mexico City in the “Reserva Ecológica del Pedregal de San Ángel” (REPSA). Standard anatomical techniques were used to obtain permanent slides of cleared leaves and transverse and paradermal sections. The permanent slides were analyzed to describe leaf architecture and anatomy by tribe following the standard terminologies.Key results: The results show a significant variation in leaf architecture although pinnate venation, brochidodromous secondary venation, areoles moderately developed and looped ultimate marginal venation predominate in the material studied. For anatomy, the most common traits are the striate cuticle, occurrence of trichomes and glands, as well as collateral vascular bundles with a parenchymatous sheath with girders in the Asteraceae present in this xerophytic scrub. There are no unique combinations of leaf characters for the family or any tribe.Conclusions: Leaf diversity in the family and within each tribe is consistent with some previous reports. Anatomical descriptions are a fundamental piece of the evolutionary, ecological and physiological studies in Asteraceae. The results of this descriptive study will allow testing hypotheses about the factors causing leaf diversity in this plant lineage. More leaf anatomical studies of the family are necessary to confirm the patterns proposed for the tribes and the family.